(untitled) (Future Cities and Environment, 2025)
Cities and urban navigation have grown increasingly complex and technologically driven in recent decades. In this evolving landscape, the emerging discourse of ’post-digital’ can potentially redirect contemporary urban discussions toward human concerns and digital affordances. Despite this shift, city/urban planning, theory, and practice have largely overlooked the transformative digital-physical impact on city navigation, missing opportunities for grounded, user-driven methodologies that post-digital studies open up. Drawing on empirically grounded case study narrative, this article investigates the forefront of urban navigation and the impact of digital technology on wayfinding practices. The research centers on post-digital navigational experiences in the New York City neighbourhoods of Flushing and Cobble Hill. The study examines personalized and innovative urban wayfinding using an experimental multi-modal framework based on recombinant spatial methods, situated actions, and conceptualizations like embodied digitality and reconfigured sociability (via blogs and vlogs). It validates that the post-digital era is shifting toward a more interactive, self-organizing, interconnected planning paradigm. This necessitates re-examining approaches to perceiving legible and navigable urban places and reworking the concept of urban narratives to better embrace today’s urban navigators’ context-aware linked experiences and viewpoints. We distill four key aspects essential for experiencing post-digital city territories: user agency, recombinant methods, hybrid wayfinding and dynamic cognitive mapping.